Aqueous phase sensing of cyanide ions using a hydrolytically stable metal–organic framework. Issue 7 (9th January 2017) - Karmakar, Avishek; Joarder, Biplab; Mallick, Abhik; Samanta, Partha; Desai, Aamod V.; Basu, Sudipta; Ghosh, Sujit K.
Abstract : A fluorescent bio-compatible anionic metal–organic framework (MOF) for pure aqueous phase recognition and detoxification of cyanide ions (CN − ) has been reported. The MOF acts as a molecular reaction vessel exclusively for cyanide ions, inducing a signal turn on response in aqueous media. Abstract : A pure aqueous phase recognition and corresponding detoxification of highly toxic cyanide ions has been achieved by a fluorescent metal–organic framework (MOF). The cyanide detoxification has been shown to be effective even in in vitro studies and the MOF could be recycled to show the same efficiency of detoxification.